The Effect of Deep Learning-Based Problem Based Learning on Students’ Learning Interest in Fifth-Grade Elementary School Mathematics - Vicky Nada Qoriah; Wahdan Najib Habiby (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aimed to analyze differences in students’ learning interest in mathematics between classes using a Deep Learning-based Problem Based Learning (PBL) approach and classes using conventional learning on whole number operations material. This study addressed the problem of low student learning interest caused by monotonous and one-way teaching methods. The study used a quantitative approach with a quasi-experimental design employing a Nonequivalent Control Group Design at MI Muhammadiyah Gonilan. The subjects consisted of 48 fifth-grade students divided into class V-A as the experimental group and class V-B as the control group. Data were collected using a Likert-scale learning interest questionnaire and observation sheets. The results showed that both groups experienced an increase in learning interest, but the experimental group demonstrated a higher improvement, with the average score increasing from 59.17 to 64.58, while the control group increased from 59.04 to 63.67. The Independent Samples T-Test results indicated a significant difference in learning interest between the two classes, showing that the implementation of Deep Learning-based Problem Based Learning was more effective than conventional learning in improving students’ learning interest in mathematics.